Rituximab in the treatment of nodal Bcell marginal zone lymphoma, primary Sjogren’s syndrome and autoimmune hepatitis - O A Logvinenko; VI Vasiljev; A M Kovrigina; N. V. Kokosadse; I. V. Gaiduk; B. V. Mitrikov; M. V. Maevskaya; E L Nasonov (Научно-практическая ревматология)
Rituximab in the treatment of nodal B- cell marginal zone lymphoma, primary Sjogren’s syndrome and autoimmune hepatitis A case of nodal B- cell marginal zone lymphoma, primary Sjogren’s syndrome and autoimmune hepatitis treated with rituximab is presented.